DETERMINANTS OF CUSTOMER SATISFACTION AND CUSTOMER LOYALTY IN THE MARKET PLACE: PRODUCT QUALITY AND SERVICE QUALITY (MARKETING MANAGEMENT LITERATURE REVIEW) - Mar’atush Sholihah (Nusantara Economics and Entrepreneurships Journals, 2023)
In the current era of globalization, life can be said to be up to date. Business conditions can be said to be very competitive between companies and other companies where the level of competition has finally become very high. Judging from the price, customers will certainly look for the lowest but do not forget to use the good quality of the product quality. From customer satisfaction that has been formed, it will later lead to loyalty from that customer. Relevant research is very important in scientific articles. Previous research or relevant research can help strengthen the theory of the relationship or influence between variables. The purpose of writing this marketing management literature review article is to build hypotheses that can be used in further research. This article reviews events that affect customer satisfaction and customer loyalty, covering: service quality and product quality in the Market Place. The results of this research literature review article are: Product quality and service quality affect customer satisfaction and customer loyalty